J.A. MacGillivray et al., Palaikastro Building I. British School at Athens Supplementary Volume 48 / C. Knappett et al., Palaikastro Block M: the Proto- and Neopalatial town. British School at Athens Supplementary Volume 47. - Wallace, Saro (Journal of Greek Archaeology, 2022)
J.A. MacGillivray and L.H. Sackett, with contributions by J.N. Bottema-Mac Gillavry, T.F. Cunningham, C. Doherty, J.M. Driessen, D. Evely, P. Jerome, O.H. Krzyszkowska, D. Mylona, D. Reese, J. Russell, A. Sarpaki, S. Wall-Crowther, P. Westlake and J. G. Younger, Palaikastro Building I. British School at Athens Supplementary Volume 48. pp. 614; col. frontispiece; 78 B/W plates; 280 B/W and col. figures (1 fold-out); 6 tables and charts (1 fold-out). London: British School at Athens, 2019. ISBN 978-0-904887-70-9, hardcover £165. C. Knappett and T. Cunningham, with contributions by D. Evely, P. Westlake and M. Bichler, Palaikastro Block M: the Proto- and Neopalatial town. British School at Athens Supplementary Volume 47. pp. 338; 36 B/W and 1 col. plates; 171 B/W figures (2 fold-outs); 6 tables and charts. London: British School at Athens, 2012. ISBN 978-0-904887-65-5, hardcover £115.